Direito à Saúde e Polícia Militar do Estado do Maranhão: uma avaliação da eficácia das políticas públicas de combate e prevenção ao suicídio no período de 2016 a 2021 - CARDOZO, Lucas Daniel Fernandes (2022)
The present work aims to discuss the limits and possibilities of public and institutional mental health policies of the Military Police of Maranhão in dealing with cases of attempts and/or suicides among military police officers. The study assumes that the weaknesses of institutional policies, because they are not broad and effective, impact the access to public mental health policies of military police, depriving them of the right of access to mental health, which consequently can impact in the increase in the number of suicides by members of the corporation. The investigation is structured in the general objective of evaluating the effectiveness of public policies to combat and prevent suicide, from 2016 to 2021, in the Military Police of the State of Maranhão, and specifically to analyze the right to access mental health as a right to health from the theory of justice developed by Rawls. To understand the relationship between mental health, suicide and the activities performed by the military police of Maranhão and, finally, to evaluate the structure of the Military Police of Maranhão, regarding access to public mental health policies for public security professionals, in the fight and suicide prevention and/or attempts in PMMA. The method of approach used was the critical-dialectical and as a method of procedure the descriptive-exploratory research, through bibliographic and documental survey, in addition to semi-structured interviews with the manager of the Corporation and professionals linked to the object of research. This is an applied, qualitative research, with an evaluation of public and institutional policies on the right of access to mental health by police officers. Therefore, the work is justified in developing an evaluation of the effectiveness of public policies on mental health by the military police of Maranhão, through the understanding of the institutional policies of the PMMA and, consequently, assistance in dealing with cases of suicides and/or attempts. From the collected results, the hypothesis is confirmed, noting that the institutional mental health policies made available to the military police are incipient, fragmented, incomplete and unstructured, which can cause mental health illnesses and difficulty in working to prevent events such as attempted suicides and completed suicides